Factors affecting Ethiopian Consumers’ Attitudes towards Purchasing Locally Produced Apparel: An Empirical Study - Eyob Minbale; Wendosen Seife (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2024)
: Currently, customers have an ever-expanding choice of purchase options owing to globalization, which leads to increased competition. Globalization and current marketing trends have made consumers more sensitive and challenging than ever. As consumers are the most important asset any business has, organizations must understand consumers’ behavior to maintain a strategic advantage in today's increased competition and globalized marketing. In this regard, this study aimed to assess the determinants of Ethiopian consumers' purchasing behavior in locally-produced apparel by using the Theory of Planned Behavior (TPB) model. Cross-sectional data from 539 consumers were collected using convenience sampling and analyzed using structural equation modeling. The structural equation model results showed that all variables had a positive and significant effect on the dependent variables, which means that all hypotheses are supported. The results also indicate that consumers' attitude toward locally produced apparel was the most influential determinant of their purchasing intention towards locally produced apparel, followed by perceived behavioral control and subjective norms. Further, consumers' purchasing intention is more influential in their purchasing behavior than perceived behavioral control. The findings of this study provide insight into domestic apparel consumption, as well as the factors affecting consumer purchasing intentions and behavior in the Ethiopian context. The results from the measurement and structural models offer key inputs for policymakers, marketers, manufacturers, and retailers.